Effects of β-glucans on the non-specific immune responses of turbot (Scophthalmus maximus L.) - Santarém, M. M.; Novoa, Beatriz; Figueras Huerta, Antonio (Fish & Shellfish Immunology, 1997)
9 páginas, 3 figuras Several non-specific immune responses of turbot (Scophthalmus maximusL.) were enhanced after the administration ofβ-glucans and/or O-antigen ofVibrio damsela. Bactericidal activity of turbot leucocytes varied depending on the bacterial virulence. Whilst no differences in bactericidal activity were observed among treated and untreated fish when a virulent strain ofV. damselawas used, leucocytes from glucan plus O-antigen-treated turbot efficiently destroyed an avirulentV. damselastrain. Respiratory burst activity was also increased seven days post-injection in leucocytes from glucan plus O-antigen-treated fish. Lysozyme activity was significantly higher in serum from fish injected with any combination of immunomodulators (glucan, O-antigen, glucan plus O-antigen) compared with controls This work was supported by Grant AGF94-1360-CO3-O3 of the Comisión Interministerial de Ciencia y Tecnología (CICYT). Peer reviewed